Energy Audit of the Footwear Factory Administration Building Using the Energy Consumption Intensity Analysis (IKE) Method - Awwalunisa Aliya Kusuma; Heri Sutanto; Muchammad Muchammad (Universitas Islam Raden Rahmat, Malang, 2025)
This study aims to enhance energy efficiency in the administrative buildings of PT. XXX's footwear factory through an energy audit. Improving energy efficiency in cooling and refrigeration systems can significantly reduce energy-related emissions due to high electricity consumption. The research method involves an energy audit in accordance with ISO 50001:2018 standards, which includes collecting historical electricity consumption data, calculating and analyze of the energy consumption intensity (IKE) and analyzing energy-saving opportunities. The analysis results indicate that the Neki A Office Marketing Building and the Bottom Office Building with an average IKE value of 17.08. The criteria building is a bit wasteful. Regarding to the analysis the significant use of electricity in every building is Air conditioning. So, the opportunity to reduce electricity and saving energy has three potentials. However, the significant impact and appropriate to implement common issue is retrofit air conditioning to inverter type. This study concludes that the implementation of energy efficiency measures can result in significant savings in electricity consumption.